1994
DOI: 10.1002/ajh.2830470210
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of gestational thrombocytopenia of <100,000/μl

Abstract: We identified 22 women with thrombocytopenia of < 100,000/microliters found incidentally during pregnancy and prospectively monitored their platelet count and clinical outcome for a minimum of 6 months postpartum. During the study period, four women became pregnant twice, accounting for a total of 26 pregnancies. The lowest platelet count during pregnancy was 65,600/microliters +/- 19,400 (mean +/- SD), and at delivery 84,500/microliters +/- 32,300 (P < 0.02). The thrombocytopenia was virtually asymptomatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
11

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 14 publications
0
25
0
11
Order By: Relevance
“…The sample size was small, and the platelet counts were not determined using a consistent protocol. However, there are only a few reports describing the clinical features of GT that are difficult to differentiate from ITP . Our study revealed that onset in the first trimester and a nadir count of less than 70 000/μL are not necessarily rare even in cases of GT, and that GT is more frequently observed in cases of twin pregnancy.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The sample size was small, and the platelet counts were not determined using a consistent protocol. However, there are only a few reports describing the clinical features of GT that are difficult to differentiate from ITP . Our study revealed that onset in the first trimester and a nadir count of less than 70 000/μL are not necessarily rare even in cases of GT, and that GT is more frequently observed in cases of twin pregnancy.…”
Section: Discussionmentioning
confidence: 48%
“…However, there are only a few reports describing the clinical features of GT that are difficult to differentiate from ITP. 4,14,17,18 Our study revealed that onset in the first trimester and a nadir count of less than 70 000/μL are not necessarily rare even in cases of GT, and that GT is more frequently observed in cases of twin pregnancy. Because of these findings, we consider our study to be of clinical significance.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…[3] gTCP is usually mild (platelet count 100 -150 × 10 9 /L), and al though the minimum threshold has never been established, counts of ≤70 × 10 9 /L are uncommon. [5] Severe TCP (≤50 × 10 9 /L) is rare, occurring in ≤0.1% of pregnancies. [6] In these cases, pathological causes of increased destruction or utilisation of platelets such as preeclampsia/eclampsia, the HELLP syndrome (haemolysis, elevated liver enzymes and low platelet count), and microangiopathies such as thrombotic thrombocytopenic purpura, (auto)immune thrombocytopenic purpura, haemolytic uraemic syndrome and haemolysis are likely.…”
mentioning
confidence: 99%
“…We performed PUBS in the 7 women with GT and an emergency cesarean section in 1 case was done due to the complication of PUBS-induced severe fetal bradycardia. [9] 1986 < 135,000 14 / 34 0 Nagey [15] 1986 < 150,000 2/ 14 0 Burrows [4] 1988 < 150,000 12 / 300 0 Kaplan [11] 1990 < 150,000 4/ 31 1 Matthews [12] 1990 < 150,000 3/ 40 0 Samuels [16] 1990 < 150,000 3/ 74 0 Copplestone [6] 1992 < 120,000 0/ 14 0 Jaschevatzky [17] 1994 < 100,000 0/ 19 0 Anteby [18] 1994 Anteby and Shalev [18] reported that maternal thrombocytopenia resolved spontaneously to more than 150,000 / mm 3 in eighteen patients within 1 month postpartum, in ve within 3 months postpartum, and in two as late as 5 months after delivery among 26 pregnancies with GT. They also showed recurrence of thrombocytopenia in four patients in the same study: three in the context of a subsequent pregnancy and in one patient who developed ITP.…”
Section: Discussionmentioning
confidence: 99%